2010
DOI: 10.1590/s1415-47572010005000049
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and biological role of the oligopeptide-binding protein (OppA) in Xanthomonas species

Abstract: In this study we investigated the prevalence of the oppA gene, encoding the oligopeptide binding protein (OppA) of the major bacterial oligopeptide uptake system (Opp), in different species of the genus Xanthomonas. The oppA gene was detected in two Xanthomonas axonopodis strains among eight tested Xanthomonas species. The generation of an isogenic oppA-knockout derivative of the Xac 306 strain, showed that the OppA protein neither plays a relevant role in oligopeptide uptake nor contributes to the infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Production of xanthan gum polysaccharide [ 2 , 3 ] induction of adhesins [ 4 , 5 ] and type III and IV effector proteins are some of the many mechanisms involved in the infection and pathogenesis [ 6 , 7 ]. The relationship between ATP-Binding Cassette systems (ABC transporters) and physiological processes has been largely demonstrated in bacteria and also in Xanthomonas genus [ [8] , [9] , [10] , [11] , [12] ]. Proteomics analyses made from leaf extracts from plants infected with X. citri revealed that more than 20% of the ABC transporters from X. citri were expressed under infection and pathogenesis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Production of xanthan gum polysaccharide [ 2 , 3 ] induction of adhesins [ 4 , 5 ] and type III and IV effector proteins are some of the many mechanisms involved in the infection and pathogenesis [ 6 , 7 ]. The relationship between ATP-Binding Cassette systems (ABC transporters) and physiological processes has been largely demonstrated in bacteria and also in Xanthomonas genus [ [8] , [9] , [10] , [11] , [12] ]. Proteomics analyses made from leaf extracts from plants infected with X. citri revealed that more than 20% of the ABC transporters from X. citri were expressed under infection and pathogenesis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%